Catalyst for polyester, preparation method and application of catalyst and preparation method of polyester

Through the preparation of MXene nano-dot catalyst, the toxic residues of antimony-based catalysts and poor dispersion of titanium-based catalysts were solved, and the production of high-performance polyester was achieved, with excellent mechanical properties and environmental protection characteristics.

CN119161567AActive Publication Date: 2024-12-20NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411376083.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-20
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing antimony-based catalysts lead to the residue of toxic metal antimony in polyester synthesis and the problems of large particles, few active sites and difficult to disperse the titanium-based catalysts, which affect the performance and environmental protection of the polyester.

Method used

Using MXene nanodot catalyst, MXene nanosheets are formed by acid or alkali etching, and nanodots are prepared in water/solvent thermal reaction, functional group regulator is added to improve surface functional groups, and a high specific surface area, rich active sites and good Dispersible catalyst.

Benefits of technology

A non-toxic metal antimony catalyst is realized, the polymerization degree and mechanical properties of the polyester are improved, the uneven dispersion problem of traditional catalysts is overcome, and a green and environmentally friendly high-performance polyester is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161567A_ABST
    Figure CN119161567A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for polyester, a preparation method and application of the catalyst and a preparation method of the polyester, and relates to the technical field of polyester synthesis. According to the preparation method of the catalyst for polyester, provided by the invention, the MXene nanosheets are formed through acid or alkali etching, then the MXene nanodots are obtained through a water / solvent thermal reaction, and the MXene nanodot catalyst suitable for polyester synthesis is prepared by adding a functional group regulator. The MXene nanodot catalyst does not contain toxic metal antimony, and also has high specific surface area, abundant active sites, abundant functional groups and good dispersity; the problems that toxic metal antimony remains in an existing antimony catalyst, and a titanium catalyst is large in catalyst particle, few in active site and difficult to disperse are solved. The MXene nanodot catalyst is adopted to prepare the polyester, so that the polyester can be endowed with functional characteristics, and the production of green, environment-friendly and high-performance polyester is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester synthesis, and in particular to a polyester catalyst, a preparation method and application thereof, and a polyester preparation method. Background Art

[0002] Polyester is a polymer formed by esterification and polycondensation of polyacids and polyols. Due to its excellent mechanical properties, thermal stability and solvent resistance, it is widely used in aerospace, electronic products, manufacturing and other fields. Catalysts are the key and difficult issues in the polyester industry. Li, Na, K, Be, Mg, Ca, Sr, Al, Ge, Sb, Ti, Mn, Fe, Co, etc. can all be used as active centers to promote polyester reactions. They exist in the reaction system in the form of oxides, esters, alcoholates, etc. At present, more than 90% of the catalysts used in polyester industrial synthesis are antimony catalysts. Studies have found that in traditional antimony catalysts, about 1 / 3 of Sb will be released in the production process, and the remaining 2 / 3 of Sb often remains in polyester and is dissolved and precipitated in large quantities during the subsequent high temperature and high pressure and ester bond breaking process, resulting in excessive heavy metal Sb content in wastewater. Many studies have shown that Sb and its compounds are toxic and carcinogenic to the human body, seriously threatening environmental safety and human health. Therefore, it is urgent to develop new green and friendly new catalysts.

[0003] Patent application CN 117285704A discloses a method for preparing a highly active titanium-based nano-polyester catalyst, which solves the problem of hydrolysis deactivation during production and transportation, and is applied to the synthesis of PBAT products with low acid value and high hue, thereby achieving the production of high-performance products. However, the resulting catalyst particles are large, have few active sites, and are still prone to agglomeration and difficult to disperse. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a polyester catalyst, a preparation method and application thereof, and a polyester preparation method. The catalyst has a high specific surface area, high catalytic activity, good dispersibility and low biological toxicity, and solves the problems of toxic metal antimony residues in antimony-based catalysts and large catalyst particles, few active sites and difficult dispersion in titanium-based catalysts.

[0005] The present invention provides a method for preparing a polyester catalyst, comprising the following steps:

[0006] S1. A MAX phase raw material is reacted with an acid solution or an alkali solution to obtain a mixture, and the mixture is post-treated to obtain MXene nanosheets, wherein M in the MAX phase raw material is a transition metal element Ti or a combination of Ti and one or more of Sc, Zr, V, Nb, Cr, Hf, Ta, W, Y and Mo, A is Al and / or Si, and X is carbon and / or nitrogen;

[0007] S2. The MXene nanosheets of step S1 are subjected to a water / solvothermal reaction in a solution containing a solvent and a functional group regulator to obtain a mixed solution containing MXene nanodots, and the mixed solution is post-treated to obtain a MXene nanodot catalyst having functional groups on the surface, wherein the particle size of the MXene nanodots is less than 20 nm, and the surface of the MXene nanodot catalyst has one or more functional groups selected from -O, -OH, -COOH, -Cl, -F, -N, -P and -S;

[0008] The preparation method of the catalyst for polyester provided by the present invention first forms MXene nanosheets by etching with acid or alkali, then obtains MXene nanodots by water / solvent thermal reaction, and then adjusts the functional groups loaded on the MXene nanodots by adding a functional group regulator, so as to obtain a MXene nanodot catalyst suitable for polyester synthesis. The MXene nanodot catalyst does not contain toxic metal antimony, and the size of the MXene nanodots is below 20nm, so that the MXene nanodot catalyst has a high specific surface area and abundant active sites. As a catalyst for polyester, it not only has efficient catalytic activity, but also its abundant functional groups on the surface react with polyester to form covalent bonds, thereby improving the interface effect between the catalyst and the polyester, improving the dispersibility of the catalyst, and thus improving the degree of polymerization of the polyester.

[0009] In a possible embodiment, the functional group regulator includes one or more of a nitrogen-containing functional group regulator, a phosphorus-containing functional group regulator, a sulfur-containing functional group regulator, a carboxyl functional group regulator, a chlorine-containing functional group regulator, a fluorine-containing functional group regulator, and a hydroxyl functional group regulator. By using the above functional group regulator, the surface of the MXene nanodot catalyst can be loaded with rich functional groups, the surface properties of the MXene nanodot catalyst can be improved, and the MXene nanodot catalyst can have better catalytic efficiency and catalytic activity.

[0010] Furthermore, the nitrogen-containing functional group regulator includes one or more of amino acids, octadecylamine, hexadecylamine, 3-aminopropyltriethoxysilane, ethylenediamine, o-phenylenediamine, aniline, p-phenylenediamine, triethylamine and triethylenetetramine.

[0011] Furthermore, the phosphorus-containing functional group regulator includes one or more of phosphoric acid, phytic acid, phospholipids, triphenyl phosphate and diphenyl phosphate.

[0012] Furthermore, the sulfur-containing functional group regulator includes one or more of dimethyl sulfoxide, ethanethiol, isopropyl mercaptan, 2-hydroxyethanethiol, m-toluene thiophenol, thioanisole and phenyl thioether.

[0013] Furthermore, the carboxyl functional group regulator is one or more of citric acid, oxalic acid, acetic acid, malonic acid, succinic acid, glutaric acid and adipic acid.

[0014] Furthermore, the chlorine-containing functional group regulator includes one or more of hydrochloric acid, sodium chlorate, calcium hypochlorite, trisodium chlorinated phosphate, sodium dichloroisocyanurate and trichloroisocyanuric acid.

[0015] Furthermore, the fluorine-containing functional group regulator includes one or more of hydrofluoric acid, sodium fluoride, 3,5-bis(trifluoromethyl)benzoic acid, 3,5-bis(trifluoromethyl)bromobenzene, 3,5-bis(trifluoromethyl)aniline, hexafluoroacetone and hexafluoroisopropanol.

[0016] The functional group regulator not only provides functional groups, but also has the advantages of easy availability of raw materials and low cost.

[0017] In a possible implementation manner, in step S2, the mass percentage of the functional group regulator in the solution is 0.1-30 wt %.

[0018] In a possible embodiment, the post-treatment process of step S1 is: the mixture is centrifuged to obtain a precipitate, the precipitate is washed with deionized water, and then after ultrasonication and centrifugation, the supernatant is collected and freeze-dried. Through post-treatment, the MXene nanosheets are separated from the mixture, and a relatively pure MXene nanosheet powder can be obtained by adopting the above post-treatment method.

[0019] Furthermore, the rotation speed of the centrifugal treatment in step S1 is ≥5000 rpm. The unreacted acid or base can be removed by the centrifugal treatment.

[0020] Furthermore, the pH value of the precipitate after washing is 5 to 8. By controlling the pH value of the precipitate after washing, it can be ensured that the acid and alkali that do not participate in the reaction are effectively removed.

[0021] In a possible embodiment, the temperature of the water / solvent thermal reaction in step S2 is 80-200° C. and the time is 10-72 hours. By controlling the temperature and time of the water / solvent thermal reaction, while ensuring the normal progress of the water / solvent thermal reaction, it is more conducive to combining rich functional groups on the surface of MXene nanodots.

[0022] In a possible implementation manner, the pH value of the water / solvent thermal reaction in step S2 is 6 to 9. By controlling the pH value of the water / solvent thermal reaction, the rate of the water / solvent thermal reaction is advantageously increased.

[0023] In a possible embodiment, the post-treatment process in step S2 is: the mixed solution is subjected to water bath ultrasound and centrifugation, and then the upper layer solution is dialyzed and freeze-dried. The MXene nanodot catalyst is separated from the mixed solution by post-treatment, and the MXene nanodot powder can be obtained by the above post-treatment steps.

[0024] Furthermore, the centrifugal speed in step S2 is ≤5000 rpm. By adopting a lower centrifugal speed, the MXene nanodots can be separated from the mixed solution while avoiding unnecessary damage to the structure of the MXene nanodots.

[0025] In a possible implementation, the solvent of the solution in step S2 is one or more of water, dimethyl sulfoxide (DMSO), ethanol, methanol, dimethylformamide (DMF), dimethylacetamide (DMAC), oleylamine and octadecylamine.

[0026] The present invention also provides a MXene nanodot catalyst prepared according to the preparation method of the above polyester catalyst, wherein the surface of the MXene nanodot catalyst has a functional group, and the functional group is one or more of -O, -OH, -COOH, -Cl, -F, -N, -P and -S.

[0027] The present invention also provides application of the polyester catalyst in the field of polyester synthesis.

[0028] The present invention also provides a method for preparing polyester, comprising the following steps:

[0029] After M1, the dibasic acid and / or dibasic acid ester and the diol are uniformly mixed, an esterification catalyst is added, and an esterification reaction is carried out under an inert atmosphere to obtain a monomer;

[0030] M2. Add the polyester catalyst mentioned above to the monomers described in step M1, and carry out polycondensation reaction under vacuum conditions to obtain polyester.

[0031] The preparation method of polyester provided by the present invention adopts a polyester catalyst (MXene nanodot catalyst) that does not contain toxic metal antimony, thereby avoiding the residue of toxic metal antimony in polyester. At the same time, the MXene nanodot catalyst also has a high specific surface area, abundant active sites, abundant functional groups and good dispersibility, which is beneficial to improving the polymerization degree and mechanical properties of polyester; and the MXene nanodot catalyst has low biotoxicity, good biocompatibility and conductivity, etc., which can give polyester functional characteristics, and is beneficial to the production of green, environmentally friendly and high-performance polyester.

[0032] In a possible implementation, the dibasic acid in step M1 is one or both of terephthalic acid and furan dicarboxylic acid.

[0033] In a possible implementation manner, the dibasic acid ester in step M1 is one or both of terephthalic acid ester and furan dicarboxylic acid ester.

[0034] In a possible implementation, the diol in step M1 is one or more of an aliphatic diol and an aromatic diol.

[0035] In a possible implementation, the molar ratio of the dibasic acid and / or dibasic acid ester to the diol in step M1 is 1.1-2.5. By controlling the usage ratio of the dibasic acid and / or dibasic acid ester to the diol, the synthesis of the monomer is more favorable.

[0036] In a possible implementation, the temperature of the esterification reaction in step M1 is 180-240° C. and the time is 2-6 hours. When the temperature and time of the esterification reaction are within the above range, a higher esterification rate can be obtained.

[0037] In a possible implementation, the amount of the polyester catalyst added in step M2 is 0.5-10‰ by mass to the theoretical polyester product. When the amount of the polyester catalyst is within the above range, it is beneficial to increase the degree of polymerization of the polyester.

[0038] In a possible implementation, the polycondensation reaction in step M2 is carried out at a temperature of 200-300° C., a time of 1-5 h, and a vacuum degree of 10-200 Pa. When the temperature, time, and vacuum degree of the polycondensation reaction are within the above ranges, the efficiency of the polycondensation reaction can be improved.

[0039] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.

[0040] The reagents and raw materials used in the present invention are commercially available.

[0041] The positive and progressive effects of the present invention are:

[0042] The present invention adopts MXene nanodot catalyst, which avoids the residual harm of toxic metal antimony in the antimony catalyst used in the prior art. At the same time, the MXene nanodot catalyst has a large specific surface area, rich functional groups on the surface, strong adsorption capacity with monomers, and high catalytic activity; MXene nanodot catalyst is easier to disperse than spherical or sheet catalysts, overcoming the problem of uneven dispersion of traditional catalysts; MXene nanodot catalyst has a strong interface effect with polyester, overcoming the problem of weak interface between catalyst and polyester; MXene nanodot catalyst has a nano-constraint effect in polyester, and can be used as a heterogeneous nucleating agent to improve the crystallization ability of polyester. The obtained polyester product has excellent mechanical properties and heat resistance, and can be widely used in engineering plastics, films, fibers and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The Ti3C2T prepared in Example 1 x Transmission electron microscopy (TEM) image of the nanodot catalyst.

[0044] Figure 2 The Ti3C2T prepared in Example 1 x X-ray photoelectron spectroscopy (XPS) curve of nanodot catalyst.

[0045] Figure 3 This is a cross-sectional SEM image of the polyethylene terephthalate prepared in Example 12.

[0046] Figure 4 This is a cross-sectional TEM image of the polyethylene terephthalate prepared in Example 12.

[0047] Figure 5 This is the visible light transmittance spectrum of the polyethylene terephthalate prepared in Example 12.

[0048] Figure 6 1 is a stress-strain curve diagram of the polyester prepared in Example 12 and Example 13. DETAILED DESCRIPTION

[0049] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0050] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0051] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0052] Example 1

[0053] This embodiment provides a Ti3C2T x Nanodot catalyst, which is prepared by the following method:

[0054] (1) The MAX phase Ti3AlC2 was placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution was added and etched in an oil bath at 35°C. After 48 hours, the solution was washed with deionized water until the pH value of the solution was greater than 5. The solution was then centrifuged at 6000 rpm to obtain a precipitate, which was freeze-dried to obtain Ti3C2T x Nanosheets;

[0055] (2) Add the Ti3C2T3 prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and water were sealed and subjected to water / solvothermal reaction at 120°C for 24 h. A mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain the Ti3C2Tx nanodot catalyst.

[0056] The transmission electron microscope (TEM) image of the Ti3C2Tx nanodot catalyst prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the average diameter of Ti3C2Tx nanodots is 2nm.

[0057] The X-ray photoelectron spectroscopy (XPS) curve of the Ti3C2Tx nanodot catalyst prepared in this example is as follows: Figure 2 As shown, XPS shows that the obtained Ti3C2Tx nanodots contain -F and -Cl functional groups.

[0058] Example 2

[0059] This embodiment provides a Ti3C2T x Nanodot catalyst, which is prepared by the following method:

[0060] (1) The MAX phase Ti3AlC2 was placed in a tetrafluoroethylene container, and then a sodium hydroxide (NaOH) solution was added. After stirring evenly, the mixture was etched at 200°C for 48 hours, washed with deionized water until the solution pH was less than 8, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze drying, Ti3C2T x Nanosheets;

[0061] (2) Add the Ti3C2T3 prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and water were sealed and subjected to water / solvothermal reaction at 120 °C for 24 h. A mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti3C2T x Nanodot catalysts.

[0062] Example 3

[0063] This embodiment provides a Ti2CT x Nanodot catalyst, which is prepared by the following method:

[0064] (1) MAX phase Ti2AlC was placed in a tetrafluoroethylene container, and then hydrofluoric acid (HF) solution was added to remove the Al in the container by etching in an oil bath at 35°C. After 48 hours, the container was washed with deionized water until the pH of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze-drying, Ti2CT was obtained. x Nanosheets;

[0065] (2) Add the Ti2CT prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and water were sealed and subjected to water / solvothermal reaction at 120 °C for 24 h. A mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti2CT. x Nanodot catalysts.

[0066] Example 4

[0067] This embodiment provides a Ti2CT x Nanodot catalyst, which is prepared by the following method:

[0068] (1) MAX phase Ti2AlC was placed in a tetrafluoroethylene container, and then hydrofluoric acid (HF) solution was added to remove the Al in the container by etching in an oil bath at 35°C. After 48 hours, the container was washed with deionized water until the pH of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze-drying, Ti2CT was obtained. x Nanosheets;

[0069] (2) Add the Ti2CT prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and ethanol were sealed and subjected to water / solvothermal reaction at 120 °C for 24 h. A mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti2CT. x Nanodot catalysts.

[0070] Example 5

[0071] This embodiment provides a Ti3C2T x- N nanodot catalyst, which is prepared by the following method:

[0072] (1) MAX phase Ti3AlC2 is placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution is added to remove the Al therein by etching in an oil bath at 35°C. After 48 hours, it is washed with deionized water until the solution pH is greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate, which is freeze-dried to obtain Ti3C2Tx nanosheets;

[0073] (2) The Ti3C2Tx nanosheets and DMF prepared in step (1) were added to a polytetrafluoroethylene reactor in sequence, and the mixture was sealed and subjected to a water / solvothermal reaction at 150°C for 18 h. A mixed solution was obtained by water bath ultrasound. The mixed solution was centrifuged at 1000 rpm for 10 min, and the upper layer solution was dialyzed and freeze-dried to obtain Ti3C2Tx nanosheets. x- N nanodot catalyst.

[0074] Example 6

[0075] This embodiment provides a Ti3C2T x- S nanodot catalyst, which is prepared by the following method:

[0076] (1) The MAX phase Ti3AlC2 was placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution was added to remove the Al therein by etching in an oil bath at 35°C. After 48 hours, the solution was washed with deionized water until the pH value of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze-drying, Ti3C2T x Nanosheets;

[0077] (2) Add the Ti3C2T3 prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and DMSO were sealed and subjected to water / solvothermal reaction at 180 °C for 15 h. The mixed solution was obtained by water bath ultrasound. After centrifugation at 1500 rpm for 8 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti3C2T x- S nanodot catalyst.

[0078] Example 7

[0079] This embodiment provides a Ti3C2T x- P nanodot catalyst, which is prepared by the following method:

[0080] (1) The MAX phase Ti3AlC2 was placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution was added to remove the Al therein by etching in an oil bath at 35°C. After 48 hours, the solution was washed with deionized water until the pH value of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze-drying, Ti3C2T x Nanosheets;

[0081] (2) Add the Ti3C2T3 prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and phosphoric acid were sealed and subjected to water / solvothermal reaction at 200 °C for 10 h. The mixed solution was obtained by water bath ultrasound. After centrifugation at 2000 rpm for 5 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti3C2T x- P nanodot catalyst.

[0082] Example 8

[0083] This embodiment provides a Ti3C2T x- N nanodot catalyst, which is prepared by the following method:

[0084] (1) The MAX phase Ti3AlC2 was placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution was added to remove the Al therein by etching in an oil bath at 35°C. After 48 hours, the solution was washed with deionized water until the pH value of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate. After freeze-drying, Ti3C2T x Nanosheets;

[0085] (2) Add the Ti3C2T3 prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and ethylenediamine were sealed and subjected to water / solvothermal reaction at 150 °C for 18 h. The mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Ti3C2T x- N nanodot catalyst.

[0086] Example 9

[0087] This embodiment provides a Nb2CT x Nanodot catalyst, which is prepared by the following method:

[0088] (1) Place the MAX phase Nb2AlC in a tetrafluoroethylene container, then add hydrofluoric acid (HF) solution, etch and remove the Al in an oil bath at 35°C, wash with deionized water until the solution pH is greater than 5 after 48 hours, then centrifuge at 6000 rpm to obtain a precipitate, and freeze-dry to obtain Nb2CT. x Nanosheets;

[0089] (2) Add the Nb2CT prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and water were sealed and subjected to water / solvothermal reaction at 150 °C for 24 h. A mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Nb2CT. x Nanodot catalysts.

[0090] Example 10

[0091] This embodiment provides a Nb4C3T x Nanodot catalyst, which is prepared by the following method:

[0092] (1) The MAX phase Nb4AlC3 was placed in a tetrafluoroethylene container, and then a hydrofluoric acid (HF) solution was added to remove the Al therein by etching in an oil bath at 35°C. After 48 hours, the solution was washed with deionized water until the pH value of the solution was greater than 5, and then centrifuged at 6000 rpm to obtain a precipitate, which was freeze-dried to obtain Nb4C3T x Nanosheets;

[0093] (2) Add the Nb4C3T prepared in step (1) into the polytetrafluoroethylene reactor in sequence. x The nanosheets and water were sealed and subjected to water / solvothermal reaction at 150 °C for 24 h. The mixed solution was obtained by water bath ultrasound. After centrifugation at 1000 rpm for 10 min, the upper layer solution was dialyzed and freeze-dried to obtain Nb4C3T x Nanodot catalysts.

[0094] Embodiment 11

[0095] This embodiment provides a polyethylene terephthalate, which is prepared by the following method:

[0096] Terephthalic acid and ethylene glycol were added into the reactor at a molar ratio of 1:3, and 0.5‰ of the Ti3C2T xThe nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 240°C. The reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, 1‰ of the stabilizer triphenyl phosphate is added, and the polycondensation temperature is set at 285°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4h. After the polycondensation is completed, polyethylene terephthalate (PET) can be obtained by discharging the material.

[0097] Example 12

[0098] This embodiment provides a polyethylene terephthalate, which is prepared by the following method:

[0099] Dimethyl terephthalate and ethylene glycol were added into the reactor at a molar ratio of 1:2.5, and Ti3C2T x The nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 220°C. The reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, 1‰ of the stabilizer triphenyl phosphate is added, and the polycondensation temperature is set at 285°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4.5h. After the polycondensation is completed, polyethylene terephthalate (PET) can be obtained by discharging the material.

[0100] Figure 3 This is a cross-sectional SEM image of the polyethylene terephthalate prepared in this example. As can be seen from the figure, the cross section of the obtained PET is smooth and no phase separation is observed, indicating that the obtained catalyst has good compatibility with PET.

[0101] Figure 4 The cross-sectional TEM image of the polyethylene terephthalate prepared in this embodiment shows that no obvious agglomeration is observed, indicating that Ti3C2T x The nanodots are well dispersed in PET.

[0102] Figure 5 This is the visible light transmittance spectrum of the polyethylene terephthalate obtained in this example. It can be seen from the figure that the light transmittance of the obtained PET film is good, and the visible light transmittance at 800nm ​​exceeds 80%.

[0103] Example 13

[0104] This embodiment provides a polyethylene furandicarboxylate, which is prepared by the following method:

[0105] Furandicarboxylic acid and ethylene glycol were added into the reactor at a molar ratio of 1:2.4, and Ti3C2T xThe nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 180°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, a stabilizer triphenyl phosphate with a mass fraction of 1‰ is added, and the polycondensation temperature is set at 235°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 5h. After the polycondensation is completed, polyethylene furandicarboxylate (PEF) can be obtained by discharging the material.

[0106] Figure 6 The stress-strain curves of the polyesters prepared in Example 12 and Example 13 show that the prepared PEF and PET have good mechanical properties. The tensile strength of PEF is >90MPa, and the elongation is greater than 5%. The tensile strength of PET is >70MPa, and the elongation is greater than 80%.

[0107] Embodiment 14

[0108] This embodiment provides a polyethylene furandicarboxylate, which is prepared by the following method:

[0109] Dimethyl furandicarboxylate and ethylene glycol were added into the reactor at a molar ratio of 1:2.2, and Ti3C2T3O4 prepared in Example 5 was added at a mass fraction of 1‰. x- The N nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 190°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, a stabilizer triphenyl phosphate with a mass fraction of 1‰ is added, and the polycondensation temperature is set at 245°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 5h. After the polycondensation is completed, polyethylene furandicarboxylate (PEF) can be obtained by discharging the material.

[0110] Embodiment 15

[0111] This embodiment provides a polybutylene furandicarboxylate, which is prepared by the following method:

[0112] Dimethyl furandicarboxylate and butanediol were added into the reactor at a molar ratio of 1:2.2, and Ti3C2T3O4 prepared in Example 5 was added at a mass fraction of 1‰. x- The N nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 175°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, a stabilizer triphenyl phosphate with a mass fraction of 1‰ is added, and the polycondensation temperature is set at 220°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 3h. After the polycondensation is completed, polybutylene furandicarboxylate (PBF) can be obtained by discharging the material.

[0113] Example 16

[0114] This embodiment provides a polyethylene furandicarboxylate, which is prepared by the following method:

[0115] Dimethyl furandicarboxylate and ethylene glycol were added into the reactor at a molar ratio of 1:2.2, and Ti3C2T3O4 prepared in Example 7 was added at a mass fraction of 1.5‰. x- The P nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 185°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, a stabilizer triphenyl phosphate with a mass fraction of 1‰ is added, and the polycondensation temperature is set at 245°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 5h. After the polycondensation is completed, polyethylene furandicarboxylate (PEF) can be obtained by discharging the material.

[0116] Embodiment 17

[0117] This embodiment provides a poly(propylene furandicarboxylate), which is prepared by the following method:

[0118] Dimethyl furandicarboxylate and propylene glycol were added into the reactor at a molar ratio of 1:2.1, and Ti3C2T x The nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 180°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, 1‰ of the stabilizer triphenyl phosphate is added, and the polycondensation temperature is set at 255°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 5h. After the polycondensation is completed, poly(propylene furandicarboxylate) (PPF) can be obtained by discharging the material.

[0119] Embodiment 18

[0120] This embodiment provides a polybutylene terephthalate, which is prepared by the following method:

[0121] Dimethyl terephthalate and butanediol were added into the reactor at a molar ratio of 1:2.3, and Ti3C2T x The nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 240°C. The reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, 1‰ of the stabilizer triphenyl phosphate is added, and the polycondensation temperature is set at 285°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4.5h. After the polycondensation is completed, polybutylene terephthalate (PBT) can be obtained by discharging the material.

[0122] Embodiment 19

[0123] This embodiment provides a poly(cyclohexane dimethanol terephthalate), which is prepared by the following method:

[0124] Dimethyl furandicarboxylate and nonanediol were added into the reactor at a molar ratio of 1:2.3, and Ti3C2T3O4 prepared in Example 1 was added at a mass fraction of 1.3‰. x The nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 225°C. The reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, a stabilizer triphenyl phosphate with a mass fraction of 1‰ is added, and the polycondensation temperature is set at 260°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4.5h. After the polycondensation is completed, polycyclohexanedimethanol terephthalate (PNF) can be obtained by discharging the material.

[0125] Embodiment 20

[0126] This embodiment provides a poly(hexane terephthalate), which is prepared by the following method:

[0127] Dimethyl furandicarboxylate and hexylene glycol were added into the reactor at a molar ratio of 1:2.1, and Ti3C2T3O4 prepared in Example 1 was added at a mass fraction of 2‰. x The nanodot catalyst is an esterification catalyst and a polycondensation catalyst. The esterification temperature is set at 210°C and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, 1‰ of the stabilizer triphenyl phosphate is added, and the polycondensation temperature is set at 255°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4.5h. After the polycondensation is completed, poly(hexane terephthalate) (PHF) can be obtained by discharging the material.

[0128] Comparative Example 1

[0129] Terephthalic acid and ethylene glycol are added into the reactor at a molar ratio of 1:3, and antimony trioxide catalyst with a mass fraction of 0.5‰ is added as an esterification catalyst and a polycondensation catalyst. The esterification temperature is set to 240°C, and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, triphenyl phosphate as a stabilizer with a mass fraction of 1‰ is added, and the polycondensation temperature is set to 285°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 20Pa) is carried out for 4h. After the polycondensation is completed, polyethylene terephthalate (PET) can be obtained by discharging the material.

[0130] Comparative Example 2

[0131] Furandicarboxylic acid and ethylene glycol are added into the reactor at a molar ratio of 1:2.4, and antimony trioxide catalyst with a mass fraction of 1‰ is added as an esterification catalyst and a polycondensation catalyst. The esterification temperature is set to 180°C, and the reaction is carried out under nitrogen protection. When the esterification rate reaches 90% of the theoretical value, triphenyl phosphate as a stabilizer with a mass fraction of 1‰ is added, and the polycondensation temperature is set to 235°C. After low vacuum pre-polycondensation (vacuum degree greater than 200Pa) for 1h, high vacuum polycondensation (vacuum degree less than 10Pa) is carried out for 5h. After the polycondensation is completed, the material can be discharged to obtain polyethylene furandicarboxylate (PEF).

[0132] The test results of tensile strength, elongation, intrinsic viscosity and chromaticity of the polyesters prepared in Example 12, Example 13, Comparative Example 1 and Comparative Example 2 are shown in Table 1. It can be seen from Table 1 that the prepared MXene quantum dot catalyst is used for the catalytic polymerization of polyester. Whether it is color, viscosity or mechanical properties, the catalytic effect of MXene quantum dots is better than that of traditional antimony trioxide catalysts. The MXene quantum dot catalyst not only has high catalytic efficiency, but is also environmentally friendly, green, non-toxic and harmless. It is a new type of efficient green catalyst.

[0133] Table 1 Comparison of mechanical properties between the examples and the comparative examples

[0134]

[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a polyester catalyst, characterized in that: The following steps are involved: S1. A MAX phase raw material is reacted with an acid solution or an alkali solution to obtain a mixture, and the mixture is post-treated to obtain MXene nanosheets, wherein M in the MAX phase raw material is a transition metal element Ti or a combination of Ti and one or more of Sc, Zr, V, Nb, Cr, Hf, Ta, W, Y and Mo, A is Al and / or Si, and X is carbon and / or nitrogen; S2. Step S1: The MXene nanosheets are subjected to a water / solvent thermal reaction in a solution containing a solvent and a functional group regulator to obtain a mixed solution containing MXene nanodots. The mixed solution is post-treated to obtain a MXene nanodot catalyst having functional groups on the surface. The particle size of the MXene nanodots is less than 20 nm, and the surface of the MXene nanodot catalyst has one or more functional groups of -O, -OH, -COOH, -Cl, -F, -N, -P and -S.

2. The method for preparing a polyester catalyst according to claim 1, characterized in that: The functional group regulator in step S2 includes one or more of a nitrogen-containing functional group regulator, a phosphorus-containing functional group regulator, a sulfur-containing functional group regulator, a carboxyl functional group regulator, a chlorine-containing functional group regulator, a fluorine-containing functional group regulator and a hydroxyl functional group regulator.

3. The method for preparing a polyester catalyst according to claim 2, characterized in that: The nitrogen-containing functional group regulator includes one or more of amino acids, octadecylamine, hexadecylamine, 3-aminopropyltriethoxysilane, ethylenediamine, o-phenylenediamine, aniline, p-phenylenediamine, triethylamine and triethylenetetramine; and / or, the phosphorus-containing functional group regulator comprises one or more of phosphoric acid, phytic acid, phospholipids, triphenyl phosphate and diphenyl phosphate; and / or, the sulfur-containing functional group regulator comprises one or more of dimethyl sulfoxide, ethanethiol, isopropyl mercaptan, 2-hydroxyethanethiol, m-thiocresol, thioanisole and phenyl thioether; and / or, the carboxyl functional group regulator comprises one or more of citric acid, oxalic acid, acetic acid, malonic acid, succinic acid, glutaric acid and adipic acid; and / or, the chlorine-containing functional group regulator comprises one or more of hydrochloric acid, sodium chlorate, calcium hypochlorite, trisodium chlorinated phosphate, sodium dichloroisocyanurate and trichloroisocyanuric acid; and / or, the fluorine-containing functional group regulator comprises one or more of hydrofluoric acid, sodium fluoride, 3,5-bis(trifluoromethyl)benzoic acid, 3,5-bis(trifluoromethyl)bromobenzene, 3,5-bis(trifluoromethyl)aniline, hexafluoroacetone and hexafluoroisopropanol; And / or, the hydroxyl functional group regulator includes one or more of water, methanol, ethanol and propanol.

4. The method for preparing a polyester catalyst according to claim 1, characterized in that: The temperature of the water / solvent thermal reaction in step S2 is 80-200° C. and the time is 10-72 h; and / or, the pH value of the water / solvent thermal reaction in step S2 is 6-9; And / or, the solvent of the solution in step S2 is one or more of water, dimethyl sulfoxide (DMSO), ethanol, methanol, dimethylformamide (DMF), dimethylacetamide (DMAC), oleylamine and octadecylamine.

5. The method for preparing a polyester catalyst according to claim 1, characterized in that: The post-treatment process of step S1 is as follows: the mixture is centrifuged to obtain a precipitate, the precipitate is washed with deionized water, and then subjected to ultrasound and centrifugation, and the supernatant is collected and freeze-dried; And / or, the post-treatment process in step S2 is: after the mixed solution is subjected to water bath ultrasound and centrifugation, the upper layer of the solution is dialyzed and freeze-dried.

6. The method for preparing a polyester catalyst according to claim 5, characterized in that: The rotation speed of the centrifugal treatment in step S1 is ≥5000 rpm; And / or, the pH value of the precipitate after washing in step S1 is 5-8; And / or, the centrifugal rotation speed in step S2 is ≤5000 rpm.

7. A catalyst for polyester, characterized in that: The polyester catalyst is a MXene nanodot catalyst prepared by the preparation method of the polyester catalyst according to any one of claims 1 to 5, and the surface of the MXene nanodot catalyst has functional groups, and the functional groups are one or more of -O, -OH, -COOH, -Cl, -F, -N, -P and -S.

8. Use of the polyester catalyst according to claim 7 in the field of polyester synthesis.

9. A method for preparing polyester, characterized in that: The following steps are involved: After M1, the dibasic acid and / or dibasic acid ester and the diol are uniformly mixed, an esterification catalyst is added, and an esterification reaction is carried out under an inert atmosphere to obtain a monomer; M2. Add the polyester catalyst according to claim 7 to the monomers described in step M1, and carry out polycondensation reaction under vacuum conditions to obtain polyester.

10. The method for preparing polyester according to claim 9, characterized in that: The dibasic acid in step M1 is one or both of terephthalic acid and furan dicarboxylic acid; And / or, the dibasic acid ester in step M1 is one or both of terephthalic acid ester and furan dicarboxylic acid ester; And / or, the diol in step M1 is one or more of aliphatic diol and aromatic diol; and / or, the molar ratio of the dibasic acid and / or dibasic acid ester to the diol in step M1 is 1.1-2.5; And / or, the temperature of the esterification reaction in step M1 is 180-240° C. and the time is 2-6 hours; And / or, the amount of the polyester catalyst added in step M2 is 0.5-10‰ by mass percentage to the theoretical polyester product; And / or, the temperature of the polycondensation reaction in step M2 is 200-300° C., the time is 1-5 h, and the vacuum degree is 10-200 Pa.

Citation Information

Patent Citations

  • Preparation method and application of high-activity titanium nano polyester catalyst

    CN117285704A

  • Preparation method of MXene-based composite metal nanodot structure gas sensor

    CN113567510A

  • MXenes compound catalyst as well as preparation method and application thereof

    CN114016057A